Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fcvm.2022.831847
|View full text |Cite
|
Sign up to set email alerts
|

The Induction of Endothelial Autophagy and Its Role in the Development of Atherosclerosis

Abstract: Increasing attention is now being paid to the important role played by autophagic flux in maintaining normal blood vessel walls. Endothelial cell dysfunction initiates the development of atherosclerosis. In the endothelium, a variety of critical triggers ranging from shear stress to circulating blood lipids promote autophagy. Furthermore, emerging evidence links autophagy to a range of important physiological functions such as redox homeostasis, lipid metabolism, and the secretion of vasomodulatory substances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 140 publications
(155 reference statements)
1
13
0
Order By: Relevance
“…It is well known that the treatment with native and oxidized low-density lipoproteins, angiostatin, homocysteine and high glucose rates can cause eNOS uncoupling, inducing a state similar to ED ( Incalza et al, 2018 ). Other works induce endothelial dysfunction through the induction of endothelial cell autophagy or through the induction of oxidative stress ( Gupta et al, 2022 ; Hua et al, 2022 ). However, from previous results of our research group in which L-NAME was used for the induction of secondary hypertension in vivo ( Fürstenau et al, 2010 ), we found the need to develop an in vitro model to mimic this condition, especially ED, following a similar method of treatment to study other aspects related to the development and establishment of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the treatment with native and oxidized low-density lipoproteins, angiostatin, homocysteine and high glucose rates can cause eNOS uncoupling, inducing a state similar to ED ( Incalza et al, 2018 ). Other works induce endothelial dysfunction through the induction of endothelial cell autophagy or through the induction of oxidative stress ( Gupta et al, 2022 ; Hua et al, 2022 ). However, from previous results of our research group in which L-NAME was used for the induction of secondary hypertension in vivo ( Fürstenau et al, 2010 ), we found the need to develop an in vitro model to mimic this condition, especially ED, following a similar method of treatment to study other aspects related to the development and establishment of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy plays a major role in many diseases, including immune diseases [ 35 , 36 ], neurodegenerative diseases [ 37 ], atherosclerosis [ 38 ], and cancers [ 39 , 40 ]. Our present work suggests that autophagy may also have a role in eosinophilic asthma.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, attention has been paid to the role of autophagy in the health of blood vessel walls ( Hua et al, 2022 ). Macroautophagy has proven important in endothelial cells (ECs) ( Torisu et al, 2016 ), vascular smooth muscle cells (VSMCs) ( Grootaert et al, 2015 ) and macrophages ( Ouimet et al, 2011 ) for maintenance of vasculature homeostasis, in response to lipid challenges and protection against atherosclerosis ( Henderson et al, 2021 ).…”
Section: Chaperone-mediated Autophagy In Stem Cellsmentioning
confidence: 99%